Adaptasi Kelompok Pamswakarsa di Pulau Lombok - , Ahmad Husni Mubarak; , Prof. Dr. Purwo Santoso, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Purpose of this study is to find out the adaptation of Independent Security Volunteers (ISVâ Pamswakarsa) in Lombok Island. In the study, ISV is seen in a form of continuous change of the preexisting entity. Methodologically, the study used a case study approach as a data collection method. Result of the study revealed that the entity called as ISV had the similarity to social protest movements promoted by village communities in the nineteenth century. The movements were popular with a term of congah. Congah was one of the forms of expressing social dissatisfactions against exploitative authority. The spirit of the movements is a social protest against the State, packaged by cultural and religious values. Congah has adapted to be ISV. The adaptation of ISV was influenced by three main factors, i.e.: change in local political setting, open political expression sphere